2023
DOI: 10.3389/fevo.2023.1007743
|View full text |Cite
|
Sign up to set email alerts
|

Scale-dependent effects of roadways on the movement behavior of a large-bodied pit viper (Crotalus horridus)

Abstract: Roadways are among the most widespread and disruptive anthropogenic land use features that influence the behavior and movement of wildlife. Negative impacts of roadways have been well documented, but the behavioral impact of roadways on smaller, cryptic species has yet to be thoroughly examined. Using a novel integration of radio telemetry and tri-axial accelerometry, we evaluated the effects of roadways on the movement behavior of 26 adult Timber Rattlesnakes (Crotalus horridus) at coarse and fine time scales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
2
1
0
Order By: Relevance
“…While small sample sizes require caution, our study does not claim any novel discoveries regarding timber rattlesnake spatial ecology, habitat selection, or thermal biology. Our observations are consistent with the ecology of the species established by decades of past field research (Reinert, 1984;Reinert et al, 1984;Reinert and Zappalorti, 1998;Waldron et al, 2006;Gardner-Santana and Beaupre, 2009;Nordberg et al, 2021;Tipton et al, 2023), including our observations of field active body temperatures and roadside habitat use (Reinert and Zappalorti, 1998;Gardner-Santana and Beaupre, 2009). Yet, our study is valuable to the road ecology conversation because it is among few that have examined the intersection of spatial, thermal, and road ecology (e.g., Peaden et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…While small sample sizes require caution, our study does not claim any novel discoveries regarding timber rattlesnake spatial ecology, habitat selection, or thermal biology. Our observations are consistent with the ecology of the species established by decades of past field research (Reinert, 1984;Reinert et al, 1984;Reinert and Zappalorti, 1998;Waldron et al, 2006;Gardner-Santana and Beaupre, 2009;Nordberg et al, 2021;Tipton et al, 2023), including our observations of field active body temperatures and roadside habitat use (Reinert and Zappalorti, 1998;Gardner-Santana and Beaupre, 2009). Yet, our study is valuable to the road ecology conversation because it is among few that have examined the intersection of spatial, thermal, and road ecology (e.g., Peaden et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…However, carcasses of turtles and large snakes were easily visible on the road because the surface of the highway was still relatively new, providing visual contrast (Supplementary Figure 7). Correlated random walk simulations indicated that rattlesnake movements were consistent with road avoidance (Supplementary Materials), which echoes numerous studies where timber rattlesnakes have demonstrated an aversion to crossing roads based on experimental trials (Andrews and Gibbons, 2005) and telemetry data collected in road fragmented landscapes (Nordberg et al, 2021;Tipton et al, 2023). Road avoidance in other species has been shown to scale with the road size and traffic intensity (Brehme et al, 2013), and the NVBP is a four-lane divided highway, with high traffic volumes (exceeding 17,000 vehicles per day) traveling at high speeds (112 km/hr).…”
Section: Discussionsupporting
confidence: 78%
“…Wildlife Management Area (WMA) in Central Georgia that was included in a radio telemetry study since 2020 (Tipton et al 2023). Snakes in this population also have been monitored since 2021 for Oo.…”
Section: Reptiles and Amphibians C O N S E R V At I O N A N D N At U ...mentioning
confidence: 99%